Pemilah Organik dengan Sensor Inframerah Terintegerasi Sensor Induktif dan Kapasitif - Bahtiar, Yusuf Ari; Ariyanto, Dedy; Taufik, Muhammad; Handayani, Trie (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2019)
Every corner of the building and room has been available bin. Not all bins have different colors. This condition makes the performance was less precise and less optimal. Often find out, still waste not match in the available place. As a result, inappropriate sorting of waste can cause problems that affect the environment. Convenience and beauty can no longer be felt. So, it needs an innovation which waste can be disposed based on its type, so that sorting and service becomes easier. "Littering Smart Detection Forms the Love Environment Mindset" the solution to trash problems. The working system of this tool uses raspberry pi as a performance brain. The embedded camera sensor will detect someone who is throwing waste. If it does not enter into the bin that is already available, a reminder and instructions will be given to make the trash dumper aware. Take back and place it in the container provided. Waste will be detected through a combination of infrared sensors and inductive and capacitive sensors. The combination of the three types of sensors that will determine the type of waste and open waste cover